The meanings of sustainable community wellness in Grabouw : exploring intersections of sustainability and wellness from a complexity thinking perspective - Van den Berg, Wessel Jan (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.